2015
DOI: 10.1097/ta.0000000000000471
|View full text |Cite
|
Sign up to set email alerts
|

Early surgical intervention for blunt bowel injury

Abstract: Prognostic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 25 publications
3
93
1
2
Order By: Relevance
“…Surgeons should make a comprehensive assessment that combines physical examination, laboratory, and radiographic findings to diagnose bowel injuries. McNutt et al [33] demonstrated that diagnostic accuracy for bowel injury becomes efficient via scoring using the Bowel Injury Prediction Score (BIPS). The BIPS includes physical examination, presence of leukocytosis, and CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons should make a comprehensive assessment that combines physical examination, laboratory, and radiographic findings to diagnose bowel injuries. McNutt et al [33] demonstrated that diagnostic accuracy for bowel injury becomes efficient via scoring using the Bowel Injury Prediction Score (BIPS). The BIPS includes physical examination, presence of leukocytosis, and CT findings.…”
Section: Discussionmentioning
confidence: 99%
“…The decisions with regard to management should be based on the combination of the results of physical examination, the presence of leukocytosis, and multidetector CT findings. The presence of leukocytosis, triangular mesenteric collections of fluid, or fluid in multiple locations is suggestive of occult bowel injury and mandates surgical exploration (14,15). A small amount of lowattenuation pelvic fluid is more reassuring.…”
Section: Invited Commentary On "Multidetector Ct Of Surgically Provenmentioning
confidence: 99%
“…These lesions occur as a result of high energy trauma involving motor vehicle accidents in 70-90% of cases. [2][3][4][5][6][7][8][9] The most common cause of HVI in our study is RTA (70%) and most of the patients were young and there is a need to focus on the preventive aspects also.…”
Section: -5mentioning
confidence: 99%
“…1 Hollow viscus and mesenteric injury are found in 3-5% of patients treated for blunt abdominal trauma (BAT). [2][3][4][5] They represent 16% of all lesions seen in BAT and in third in order of frequency after liver and splenic injury. Hollow viscus injury (HVI) is difficult to diagnose and any delay in diagnosis will eventually increase the morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%